Encoding of virtual acoustic space stimuli by neurons in ferret primary auditory cortex. - Mrsic-Flogel, T; King, A; Schnupp, J (2005)
Recent studies from our laboratory have indicated that the spatial response fields (SRFs) of neurons in the ferret primary auditory cortex (A1) with best frequencies > or =4 kHz may arise from a largely linear processing of binaural level and spectral localization cues. Here we extend this analysis to investigate how well the linear model can predict the SRFs of neurons with different binaural response properties and the manner in which SRFs change with increases in sound level. We also consider whether temporal features of the response (e.g., response latency) vary with sound direction and whether such variations can be explained by linear processing. In keeping with previous studies, we show that A1 SRFs, which we measured with individualized virtual acoustic space stimuli, expand and shift in direction with increasing sound level. We found that these changes are, in most cases, in good agreement with predictions from a linear threshold model. However, changes in spatial tuning with increasing sound level were generally less well predicted for neurons whose binaural frequency-time receptive field (FTRF) exhibited strong excitatory inputs from both ears than for those in which the binaural FTRF revealed either a predominantly inhibitory effect or no clear contribution from the ipsilateral ear. Finally, we found (in agreement with other authors) that many A1 neurons exhibit systematic response latency shifts as a function of sound-source direction, although these temporal details could usually not be predicted from the neuron's binaural FTRF.